Ta’tsîr Itqân al-Mufradât ‘ala Qudrah Hifdz al-Quran li Tilmîdzât al-Fasl al-tsâlis A - Luthfatul Qibtiyah; Nur Faradila; Izzat Amini (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2023)
Mastery of Arabic vocabulary is the ability to use the words you have in communicating and making it easier to memorize Arabic texts, especially memorizing the Al-Qur'an. The aim of this research is to determine the effect of vocabulary mastery on the ability to memorize the Qur’an and the size range of the third class “A” female students at the Al-Amin Brandwan Institute for the Memorization of the Qur’an. The research used quantitative input. The two variables are vocabulary proficiency (the independent variable) and the ability to memorize the Qur'an (the dependent variable). The community in this research is the students of the Institute for Memorizing the Qur’an, third semester “A”, numbering 36 students. To collect the data, the researcher used a questionnaire and documentation. And the data analysis method used is simple linear regression analysis using SPSS for Windows 20. Data analysis results using a simple linear regression equation that the output value is t count value = 2.482 with significant level 0.000 < 0.05, which means that vocabulary mastery (independent variable) There is an effect on the ability Memorizing the Qur’an (dependent variable).